A Study in Design and Comparison of Reinforced, Prestressed and Partially Prestressed Pier Cap over a Rectangular Hammerhead Pier - Gandhi, Arooshree (My University, 2018)
Nowadays, the designers in the field are required to design six lane structures like ROBs, RUBs and flyovers. Further, these structures need to be supported on a wider sub structure. In case of cross drainage structures, the provision of a wider sub structure can be feasible because of no traffic flow below it, but in case of grade separators like ROBs and flyovers, the space constriction and inability to find clear height, doesn’t allow us to provide the required depth for the reinforced concrete Pier cap. To decrease the depth and to increase the moment and shear capacity, the scope of this thesis is to see the effect of prestressing or partial prestressing on those parameters. An analytical method was used to develop spread sheets for design of Reinforced Concrete, Prestressed Concrete and Partially Prestressed Concrete Pier Caps as per the IS and IRC codes taking into account factors incorporating both serviceability and ultimate limit states. Furthermore, a separate section of this thesis describes a comparative study of three different categories of prestressing i.e. no prestress, partial prestress and fully prestressed pier caps. The relationship of each of these to the serviceability parameters is considered. Finally, the cost comparison was done to calculate the most viable type of structure.
Master of Engineering- Structures
Keywords: Reinforced concrete; Prestressed Concrete; Pier Cap; Hammer Head Pier; Partial Prestressed